PENGUKURAN DAN PENILAIAN KUALITAS UDARA DALAM RUANG PADA HUNIAN RUMAH SUSUN : STUDI KASUS RUSUNAWA TINGKULU MANADO - Al Asy' Ary, Muhammad Farid; Sangkertadi, Sangkertadi; Waani, Judy O. (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
Abstract: Measurement and Evaluation of Indoor Air Quality in Residential Low – Income Apartment : Case Study of Rusunawa Tingkulu Manado This research aims to determine the air quality in the residential space of Rusunawa Tingkulu. Indoor air quality is very vulnerable to exposure to pollution both from outside and inside the room. Poor air quality can be a contributing factor to the health and comfort of occupants of residential spaces. The focus of this research is to determine and identify air quality variables in residential spaces, namely on physical quality such as wind speed, air temperature, relative humidity, Pm2.5, Pm10, and chemical quality such as CO₂, HCHO, VOC, and O₂ levels. The method used in this research is field observation using measuring instruments as instruments for measuring variables that affect indoor air quality. Air quality data obtained from measurements are compared with standard data on ideal air requirements in the home space referring to the Regulation of the Minister of Health of the Republic of Indonesia. The data is then described in the form of graphs and tabulations, then explained descriptively. From the results of the measurements taken, it was found that the physical quality and chemical quality of CO₂ in residential spaces did not meet the required standards. Meanwhile, chemical quality variables such as HCHO, VOC, and O₂ levels have met the ideal air quality standards in residential spaces.